Influência da heterogeneidade de rejeitos de minério de ferro utilizados como adição mineral nas propriedades de microconcretos - Bruna Silva Almada (2021)
Iron mining, despite having a positive impact on the economy, is associated with a relevant environmental issue, due to the extensive altered areas and the large volume of waste generated in the extraction and processing process. With the growth of mining activity, increasingly, dams have become bigger, which makes their management difficult and can lead to their collapse. Therefore, the use of iron ore tailings (IOT) contributes to the reduction of environmental impacts, in addition to adding value to another product. Due to their granulometry and chemical composition, IOT’s has potential for use as a raw material in products intended for civil construction, for example in cementitious materials. However, different exploited deposit and ore beneficiation process can generate waste with different physical-chemical and mineralogical properties. Therefore, when it is introduced in some material, its heterogeneity can lead to different results in the final composite mechanical and durability performance. In view of this, this work aims to assess whether the heterogeneity of IOT’s influences the properties of microconcretes, when the tailings are applied as an addition. Four iron ore tailings from different mines were collected and added to microconcrete in a 40% contente, in relation to the cement mass. The tailings were characterized in terms of chemical composition and physical and mineralogical characteristics to verify heterogeneity. Then, microconcrete specimens were molded to evaluate the mechanical and microstructural properties and durability indicators. In general, the IOT particles acted by filling the pores, promoting maintenance or improvement of properties. The results indicated a tendency to improve mechanical strength, increase stiffness and reduce porosity. Thus, there are indications of improved durability, such as reduced carbonation. The hardness and indentation module of the cementitious matrix tend to be increased with the introduction of IOT. However, the influence of each RMF on the microconcrete was variable for some properties, indicating that the heterogeneity of this residue must be a factor considered for different applications of the material. This research collaborates with the expansion of knowledge regarding the microstructure of composites containing addition of IOT. In addition, it reiterates the importance of using industrial by-products in civil construction as a solution to the environmental impacts associated with waste.